2013
DOI: 10.1177/1087054713489849
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Illusory Bias in Children and Adolescents With ADHD

Abstract: Results support the presence of the positive illusory bias also in the domain of everyday life activities. Improvement of self-evaluation of competencies should become a focus of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…Children (Wiener et al, 2012) and adolescents (Barkley et al, 2002; Sibley et al, 2012, 2017) with ADHD report fewer ADHD symptoms relative to their parents and/or teachers. Consistent with the ignorance of incompetence hypothesis (which postulates that individuals who have poorly developed skills in a given domain are unable to recognize their incompetence in that domain, Kruger & Dunning, 1999), the SPB in children with ADHD has been found to be most evident in their domains of greatest deficit (Hoza et al, 2002, 2004; Volz-Sidiropoulou et al, 2016). Furthermore, co-occurring depressive symptoms are associated with increased accuracy of self-perceptions in children with ADHD (see Jiang & Johnston, 2014, for review).…”
mentioning
confidence: 75%
“…Children (Wiener et al, 2012) and adolescents (Barkley et al, 2002; Sibley et al, 2012, 2017) with ADHD report fewer ADHD symptoms relative to their parents and/or teachers. Consistent with the ignorance of incompetence hypothesis (which postulates that individuals who have poorly developed skills in a given domain are unable to recognize their incompetence in that domain, Kruger & Dunning, 1999), the SPB in children with ADHD has been found to be most evident in their domains of greatest deficit (Hoza et al, 2002, 2004; Volz-Sidiropoulou et al, 2016). Furthermore, co-occurring depressive symptoms are associated with increased accuracy of self-perceptions in children with ADHD (see Jiang & Johnston, 2014, for review).…”
mentioning
confidence: 75%
“…For example, several studies have shown that children, adolescents and adults with ADHD show a ‘positive illusory bias,’ as defined by ‘a self-enhancing discrepancy between self-reports of competence and external indices of competence, such as ratings by other informants (e.g. teachers, parents, peers) or objective measures of performance’ (Emeh et al 2015 ; Hoza et al 2010 ; Prevatt et al 2012 ; Volz-Sidiropoulou et al 2016 ). However, more realistic and lower levels of self-reflections have also been found in adults with ADHD (Fuermaier et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…PIB has emerged in a wide range of areas such as academic abilities, social abilities, behavioural symptoms, activities of daily living (e.g. daily cognitive requirements, graphomotor skills, executive tasks), and difficult physical activities for children with ADHD (Helseth, Bruce, & Waschbusch, 2016;Hoza et al, 2004;Volz-Sidiropoulou, Boecker, & Gauggel, 2016). Children with ADHD generally overestimate their abilities across multiple domains of functioning, such as behavioral, scholastic and social domains (Bourchtein et al, 2017).…”
Section: Positive Illusory Bias Paradigmsmentioning
confidence: 99%